2011
DOI: 10.1007/s13149-011-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

Le rétrovirus humain oncogène HTLV-1 : épidémiologie descriptive et moléculaire, origine, évolution et aspects diagnostiques et maladies associées

Abstract: Human T-cell leukemia/lymphoma virus type 1 (HTLV-1) was the first oncogenic human retrovirus discovered in 1980. It is estimated that around 10-20 million people are infected with HTLV-1 worldwide. However, HTLV-1 is not a ubiquitous virus. Indeed, HTLV-1 is present throughout the world with clusters of high endemicity including mainly southern Japan, the Caribbean region, parts of South America and intertropical Africa, with foci in the Middle East and Australia. The origin of this puzzling geographical repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 89 publications
1
8
0
1
Order By: Relevance
“…Our results indicate that infection by the herpesviruses CMV, LCV and RRV and by the retrovirus SFV is frequent and often acquired early in life in the macaque population studied. These results are generally in keeping with published data (Chu et al, 1971;Ishida and Varavudhi, 1992;Ryan and Rose, 2013;Vogel et al, 1994;Calattini et al, 2006;Jones-Engel et al, 2007Muniz et al, 2015) although the macaque colony in Gibraltar was found to be CMV negative, for reasons not fully understood . Transmission is thought to occur via the oral route and/or through bites and scratches.…”
Section: Discussionsupporting
confidence: 90%
“…Our results indicate that infection by the herpesviruses CMV, LCV and RRV and by the retrovirus SFV is frequent and often acquired early in life in the macaque population studied. These results are generally in keeping with published data (Chu et al, 1971;Ishida and Varavudhi, 1992;Ryan and Rose, 2013;Vogel et al, 1994;Calattini et al, 2006;Jones-Engel et al, 2007Muniz et al, 2015) although the macaque colony in Gibraltar was found to be CMV negative, for reasons not fully understood . Transmission is thought to occur via the oral route and/or through bites and scratches.…”
Section: Discussionsupporting
confidence: 90%
“…The four HTLV types, 1 to 4, in humans have each simian counter-parts (STLV-1 to 4) (Le Breton et al 2014; Gessain 2011; Gessain et al 2013). HTLV-1 and 2 are relatively widespread and are estimated to infect around 20 million people, but HTLV-3 and HTLV-4 have only been documented in a handful of indivuduals in central Africa (Gessain et al 2012; Mahieux et al 2011; Richard et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of carriers are asymptomatic, with only 3-7% of affected people presenting with clinical manifestations (2) . The clinical spectrum of the disease encompasses infective dermatitis (IDH), HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/ TSP), and adult T-cell leukemia lymphoma (ATLL) (3) .…”
Section: Discussionmentioning
confidence: 99%